Drug risk Factors Associated with a Sustained Outbreak of Clostridium difficile Diarrhea in a Teaching Hospital - Swapan K Nath; Suzette Salama; Devia Persaud; James H Thornley; Ian Smith; Gary Foster; Coleman Rotstein (Canadian Journal of Infectious Diseases)
A case-control study was undertaken to identify and quantify antimicrobial and nonantimicrobial drug risk factors associated with a sustained outbreak of Clostridium difficile diarrhea on two medical (teaching and nonteaching) units and an oncology unit. In total, 80 cases associated with an endemic clone of toxigenic C difficile were compared with controls. Eighty controls were selected from a group of 290 controls randomly chosen from the outbreak period. The controls were matched to cases according to age, admitting diagnosis and unit of admission. Seventy (88%) patients in the case group received at least one antibiotic before diarrhea, compared with 37 (46%) patients in the control group. Major risk factors implicated in the development of C difficile diarrhea in hospitalized patients were the following antimicrobial agents: ceftazidime (adjusted odds ratio [aor]=26.01, 95% ci 5.67 to 119.19, P=0.0001); cefuroxime (aor=5.17, ci 1.86 to 14.36, P=0.005); ciprofloxacin (aor=3.81, ci 1.05 to 13.79, P=0.04); and clindamycin (aor=15.16, ci 2.93 to 78.44, P=0.004). This is the first time that the use of ciprofloxacin has been linked to the development of C difficile diarrhea. Use of gastrointestinal drugs (ranitidine, famotidine, cimetidine, omeprazole and sucralfate) was also an added risk (aor=3.20, ci 1.39 to 7.34, P=0.01); however, antineoplastic therapy was not significant (P<0.53). Recognition of the specific high risk drugs may spur more restricted use of these agents, which may help in controlling C difficile diarrhea in hospitalized patients.